(untitled) (Conference Zone, 2022)
In this article, the issue of child upbringing in Uzbek families, Eastern thinkers in child upbringing Muhammad ibn Musa al-Khorazmi, Abu Nasr Farabi, Abu Rayhan Beruni, Abu Ali ibn Sina, Muhammad Kashghari, Yusuf Khos Khajib, Kaikovus, Omar Khayyam, Ahmad Yugnaki , information on the issues of raising children in the family in a number of works of thinkers such as Husayn Vaiz Koshifi.